Methane production from the co-digestion of pig manure and corn stover with the addition of cucumber residue: Role of the total solids content and feedstock-to-inoculum ratio. (June 2020) - Wang, Yaya; Zhang, Jiaxing; Li, Yangyang; Jia, Shufei; Song, Yang; Sun, Yanbo; Zheng, Zehui; Yu, Jiadong; Cui, Zongjun; Han, Yiyu; Hao, Jianjun; Li, Guoxue
Highlights: The methane yield mainly decreased with increasing TS content and F/I ratio. The TS content of 10% was mostly affected by an increased F/I ratio. The Kh and Rmax decreased with increasing TS content and F/I ratio. A TS content of 30% had the highest net present value and internal rate of return. SS-AD were financially attractive especially at a lower F/I ratio. Abstract: This study investigated performance and stability of increasing total solids (TS) content (10–30%) and feedstock-to-inoculum (F/I) ratios (1, 2) on anaerobic co-digestion of agricultural wastes. The cumulative methane yields generally decreased with the increasing TS content except for the TS content of 30% at F/I ratio of 1 and TS content of 10% at F/I ratio of 2. This was consistent with the maximum methane production rate (Rmax ) and rate of the hydrolysis (Kh ) stage in reactors. The pH, VFAs and NH4 + -N content were positively correlated with increasing TS contents and F/I ratios. Economic analysis results indicated the net present value generally increased with increasing TS contents and TS content of 30% at F/I ratio of 1 had the highest net present value (5.7 million US$) and internal rate of return (41.9%). This indicated solid-state anaerobic digestion was financially attractive under analyzed conditions.